1935
DOI: 10.1017/s0031182000015262
|View full text |Cite
|
Sign up to set email alerts
|

On the Persistence of Eosinophilia, and on Immune Reactions in Human Trichinosis, Several Years after Recovery

Abstract: Following a brief historical introduction, the results of differential counts, precipitin tests and skin reactions on seven cases of trichinosis 4–9 years after recovery are presented. Eosinophile counts ranging from 2 to 7 per cent. were encountered, but the number of cases studied does not warrant any conclusion being drawn. Positive precipitin tests and intradermal reactions were encountered in cases up to 7 years after infection. The findings are discussed, together with a consideration of the pertinent li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1936
1936
1987
1987

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The epicuticle is still a somewhat enigmatic structure, despite a recent freeze-fracture study which showed that it has an unusual ' fingerprint-like' appearance in fracture replicas, that was taken to indicate a cholesterol-rich composition (Lee, Wright & Shivers, 1984). There is no doubt that the epicuticle can be readily shed by cultured parasites (unpublished data) and if it is also shed in vivo, then it would stimulate continued synthesis of specific antibody during infection (Theiler, Augustine & Spink, 1935;Pritchard, 1977). Pritchard has recently presented evidence that excretory/secretory antigens are produced by encysted muscle-stage larvae in vivo and that these antigens are taken up by immunocompetent cells located ' within' developing cysts (Pritchard, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…The epicuticle is still a somewhat enigmatic structure, despite a recent freeze-fracture study which showed that it has an unusual ' fingerprint-like' appearance in fracture replicas, that was taken to indicate a cholesterol-rich composition (Lee, Wright & Shivers, 1984). There is no doubt that the epicuticle can be readily shed by cultured parasites (unpublished data) and if it is also shed in vivo, then it would stimulate continued synthesis of specific antibody during infection (Theiler, Augustine & Spink, 1935;Pritchard, 1977). Pritchard has recently presented evidence that excretory/secretory antigens are produced by encysted muscle-stage larvae in vivo and that these antigens are taken up by immunocompetent cells located ' within' developing cysts (Pritchard, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Higher magnification ( x 1250) revealed that the cells were ungranulated and mononuclear in nature (2 c, 2d). levels of immunity and circulating host serum antibodies observed during infection with this parasite (THEILER et al, 1935;PRITCHARD, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Trawinski [61] -considers that the phenol in Coca's solution can give rise to precipitation using normal sera. The persistence of both these immune reactions in man, four to nine years after -recovery from trichinosis, has been reported by Theiler, Augustine, and Spink [60].…”
Section: Immunological Reactionsmentioning
confidence: 60%